2019
DOI: 10.3389/fnins.2019.01119
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Matching in Cochlear Implant Users With Single-Sided Deafness: Effects of Electrode Position and Acoustic Stimulus Type

Abstract: Previous studies in patients with single-sided deafness (SSD) have reported results of pitch comparisons between electric stimulation of their cochlear implant (CI) and acoustic stimulation presented to their near-normal hearing contralateral ear. These comparisons typically used sinusoids, although the percept elicited by electric stimulation may be closer to a wideband stimulus. Furthermore, it has been shown that pitch comparisons between sounds with different timbres is a difficult task and subjected to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…One possible reason for the disparate results across studies is that the procedures (Jensen et al, 2021) and stimuli (Adel et al, 2019) employed had a large impact on the observed results, which questions whether these measurements reflect place of stimulation. In the current study, the surprising tonotopic pattern of pitch-match estimates for SSD-CI listeners (positive at the apex, negative at the base, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason for the disparate results across studies is that the procedures (Jensen et al, 2021) and stimuli (Adel et al, 2019) employed had a large impact on the observed results, which questions whether these measurements reflect place of stimulation. In the current study, the surprising tonotopic pattern of pitch-match estimates for SSD-CI listeners (positive at the apex, negative at the base, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To address the question of plasticity to interaural place mismatch more directly, the current study explicitly compared interaural place-pitch perception and tuning curves for interaural time-difference (ITD) sensitivity to estimates of electrode position derived from computed-tomography (CT) scans. Previous studies have compared pitch matching and ITD discrimination for BI-CI users (Hu and Dietz, 2015), or pitch matching and CT scans for SSD-CI users (Schatzer et al, 2014; Adel et al, 2019), but the three measurements have never been compared. We hypothesized that evidence for plasticity would differ between the two perceptual measures: binaural sensitivity would not show evidence of plasticity, with ITD-based estimates aligning closely with CT-based estimates of electrode location, while interaural place pitch would show evidence of plasticity, with pitch-based estimates aligning more closely with clinical center frequencies (CFs) in the CI map.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that pitch matching of electric and contralateral acoustic stimuli can be a difficult task ( Adel et al., 2019 ; Carlyon et al., 2010 ; Schatzer et al., 2014 ). Carlyon et al.…”
Section: Discussionmentioning
confidence: 99%
“…In both loudness balancing and pitch matching experiments, pairs of stimuli were presented with a 300-ms gap. The suitability of different types of acoustic stimuli including pure tones, narrow band noise, and filtered harmonic stimuli in electric-acoustic pitch matching experiments has been analyzed in the literature ( Adel et al., 2019 ; Carlyon et al., 2010 ). Adel et al.…”
Section: Methodsmentioning
confidence: 99%
“…The 250 Hz pure tone (es20) activated the most apical electrode only (electrode 20), while the 1050 Hz pure tone (es14) activated electrode 14 and 13. Such tasks have been performed in previous studies [7], [8], [17][18][19][20][21][22]. However, in these studies, the pulse rate was set to a level either below 40 or above 700 pps in order to minimize the temporal pitch cues.…”
Section: Pitch Matchingmentioning
confidence: 99%